2006
DOI: 10.1007/s00114-006-0129-7
|View full text |Cite
|
Sign up to set email alerts
|

Induced resistance enzymes in wild plants–do ‘early birds’ escape from pathogen attack?

Abstract: Systemic acquired resistance (SAR) of plants to pathogens is a well-defined phenomenon. The underlying signalling pathways and its application in crop protection are intensively studied. However, most studies are conducted on crop plants or on Arabidopsis as a model plant. The taxonomic distribution of this phenomenon and its dependence on life history are thus largely unknown. We quantified activities of three classes of resistance-related enzymes in 18 plant species to investigate whether plants with varying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…The activities of the defence-related enzymes cinnamyl alcohol dehydrogenase (CAD, EC 1.1.1.195) and peroxidase (POX; EC 1.11.1.7) were determined as described by Boyle and Walters (2006), while β-1,3-glucanase (EC 3.2.1.6) was determined as described by Heil and Ploss (2006). The enzyme assays were scaled down in order to allow them to be carried out using 96-well microtitre plates.…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…The activities of the defence-related enzymes cinnamyl alcohol dehydrogenase (CAD, EC 1.1.1.195) and peroxidase (POX; EC 1.11.1.7) were determined as described by Boyle and Walters (2006), while β-1,3-glucanase (EC 3.2.1.6) was determined as described by Heil and Ploss (2006). The enzyme assays were scaled down in order to allow them to be carried out using 96-well microtitre plates.…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…(Taylor and Markham 1978). Heil and Ploss (2006) reported minimal induced disease resistance in lesser celandine but noted that its ephemeral habit may allow it to grow and reproduce under low pathogen pressure. The ephemeral nature of lesser celandine reduces viable biocontrol options.…”
Section: Potential For Biological Controlmentioning
confidence: 97%
“…This hypothesis has been tested on various occasions with positive results. In an interesting study on inducibility of defense-related enzymes in wild plants against pathogen attack, Heil & Ploss (2006) found that plants characterized by different life histories appear to have evolved different strategies to defend themselves against pathogens. These ranged from species differing in longevity (annual or perennial), leaf-shedding manner (evergreen or deciduous), latitudinal range, and level of drought experienced in the native habitat.…”
Section: Herbivorymentioning
confidence: 99%